Effectiveness of community-based personalized breastfeeding assessment and intervention in improving child growth among 0–4 months infants - Pranita Priyadarshini Nayak,; Akanksha Tomar,; Preeti Gupta, (Asian Journal of Medical Sciences, 2025)
Background: Breastfeeding is critical for infant health, yet suboptimal practices persist due to sociocultural and structural barriers, especially in low-resource urban settings. This study evaluated the effectiveness of community-based, personalized breastfeeding assessments and interventions in improving infant growth among infants aged 0–4 months residing in urban slums of Jabalpur, India. Aims and Objectives: The primary objective was to assess breastfeeding techniques and child growth among lactating mothers, with a focus on intervening using correct positioning and attachment methods when necessary. A secondary objective was to monitor infant growth biweekly for 2 months among mothers initially exhibiting improper techniques. Materials and Methods: A community-based interventional study was conducted in three urban slum areas, enrolling 61 lactating mothers. Breastfeeding practices were assessed using structured questionnaires and direct observation. Mothers practicing suboptimal techniques received immediate corrections through hands-on demonstrations and educational videos. Infant growth was monitored biweekly using WHO growth charts and data were analyzed with SPSS 20 using a mixed-effects regression model. Results: Results indicated that initially, only 3% of mothers practiced effective breastfeeding. However, after four follow-up visits, 70% of mothers had adopted proper techniques. Significant improvements were observed in recognizing hunger cues, hand hygiene before feeding, and breastfeeding frequency. Infant weight gain met expectations in a majority of cases, with maternal education emerging as an influential factor. Conclusion: The prevalence of effective breastfeeding practices in Jabalpur’s slum populations is very low. Repeated, targeted interventions by community health workers can enhance breastfeeding techniques and contribute to improved child growth outcomes.